Seasonal effects on puberty and reproductive characteristics of female Chios sheep and Damascus goats born in autumn or in February - Koumas, Alkis; Photiou, C.; Papachristoforou, Christakis (My University, 2000)
Ten Chios ewe lambs and 10 Damascus she-kids born in October–November and similar numbers born in February along with eight multiparous females from each species, were used to examine pubertal events and reproductive seasonality. Reproductive activity was monitored by determining serum progesterone concentrations once a week for 12 months. The mean date of onset of ovulation (puberty) in autumn-born Chios females (7 August) was earlier (p<0.05) than in February-born ones (11 September) though the onset of regular cyclicity was not significantly different between the two groups (30 August and 19 September, respectively). The age and live weight at puberty in autumn-born females was higher (p<0.01) than in February-born ones, the respective values being 43.3 weeks and 50.1 kg, versus 29.9 weeks and 42.0 kg. All animals, irrespective of time of birth, started ovulating after the summer equinox. Multiparous Chios ewes had reproductive cycles covering most time of the year with acyclic periods during spring and summer. In ewe lambs, about half of the animals ceased cycling during the second half of winter and in spring, while the rest continued cycling. The total number of cycles detected over the experimental period was lower (p<0.05) for February-born (n=9.4) compared with autumn-born females (n=13.7) and adult ewes (n=17.1). In Damascus she-kids born in autumn or in February, onset of puberty was at the same time in the following autumn, the respective mean date for the two groups being 1 November and 27 October. For autumn-born animals, age (48.4 weeks) and live weight (53.8 kg) at puberty were higher (p<0.01) than for those born in February (37.3 weeks, 42.9 kg). Reproductive cycles in adult goats started in the second half of September and continued until the end of March. Most young goats (75%) had their last seasonal cycle in February and the rest in March. The total number of cycles was higher (p<0.01) in adult (n=8.1) than in young goats born either in autumn (n=6.3) or in February (n=5.7). It is concluded that reproductive development and puberty in Chios female sheep are mostly under seasonal influences though age and body weight are also contributing factors. This breed has a long reproductive season with some animals cycling throughout the year. The Damascus female goat is strictly seasonal with distinct periods of reproductive cyclicity and inactivity. Puberty attainment of Damascus females born in autumn or in February is at the same time the following autumn.
Keywords: Chios sheep; Damascus goats; Puberty; Season